Letramento digital e formação de professores: limites e potencialidades na perspectiva do plano nacional de formação de professores (PARFOR) - Ataíde, Denyse Mota da Silva (Universidade Federal do Tocantins, 2016)
In this thesis we present the results of a survey conducted at the Federal University of Tocantins (UFT) Araguaína campus. The goal was to identify, describe and analyze the digital literacy practices, focusing on the Course of Literature of the National Teacher Training (PARFOR), reaching teachers and trainers in training, evaluating their interactions in the construction of knowledge (continuing education) , mediated by computer and its artifacts. The method chosen to conduct our research is limited to the field of phenomenology, based on theoretical studies of Oliveira and Cunha (2007), featuring the phenomenological method as one that seeks to understand the phenomenon questioned, not bothering with explanations and / or generalizations, since the researcher is not part of a specific problem, but conducts research from a question about a phenomenon which needs to be situated and experienced by the subject. How to approach our research is configured as quantiqualitative and case study. It is qualitative since his approach is essentially descriptive and its inductive procedures, considering the existence of a dynamic relationship between the real world and subject, as Ludke and Andrew (1986); Alves-Gewandsznajder and Mazzotti (1999); Severino (2000); Duarte (2002), and Marconi and Lakatos (2006), and the process is the main focus. It is a case study considering the study Sturman (1988). The theories that underlie our research include: literacy; literacies; cyberculture, reading, writing, teacher training NTCIs; teaching practice and the different contexts in which pass all these occurrences. To use the theories of literacy, a higher proportion of jobs Kleiman (1995, 1998, 2006), Soares (1995, 1998, 2002, 2003), Heath (1983, 2004), Street (2003), Barton (1994). About digital literacy, Buzatto (2003; 2007); Freitas (2010); Leffa (2005); Machado and Teruya (2009); Noveleto and Claus (2009); About Teacher training, Pine (2007); Rock and Pine ( 2011); Gastti (2000); Pimentel (2006. Results show that even before the troubles faced by teachers of public schools in Tocantins, they unfold in order to conduct a continuing education that will improve their teaching performance, and PARFOR presents itself as a real possibility. From this perspective, the fact of making a blended course, contributes to that enforce digital literacy practices, which favors life in society. study found that students of letters PARFOR of the UFT Araguaína face some difficulties when they have to deal with new technologies, in the case studied here, the computer and its digital tools. Nevertheless, computer literacy takes place, even at the expense of difficulties, such as access to virtual environment Moodle, when need to access the contents that are posted by professors online.